Advances in Techniques for Intact Removal of Permanently Cemented Restorations: A Systematic Review - Tawade, Shubham; Dhamande, Mithilesh; Godbole, Surekha; Borle, Anjali; Sathe, Seema; Gupta, Ashish; Pophali, Mrunmayee (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Permanent cemented restorations, such as crowns, bridges, and inlays, are integral to restorative dentistry due to their durability and functional benefits. However, their removal remains challenging, as conventional techniques often risk damaging the underlying tooth structure. Recent advances, including laser-assisted and ultrasonic methods, offer minimally invasive alternatives thatimprove safety and efficiency. This systematic review aims to evaluate and compare contemporary techniques developed for the intact removal of permanently cemented restorations, assessing their efficacy, safety, and clinical applicability relative to traditional methods.Methods: A comprehensive search was conducted across PubMed, Scopus, Web of Science, and Google Scholar for studies published between 2000 and 2024. Keywords included “cemented restorations,” “crown removal,” “laser-assisted debonding,” and “ultrasonic instruments.” Studies focusing on mechanical, chemical, laser-assisted, and ultrasonic techniques for restoration removal were included. Data extraction focused on technique type, mechanism of action, outcomes, and clinical success. Narrative synthesis was performed due to heterogeneity among studies.Results: Thirty-five studies met the inclusion criteria. Laser-assisted techniques, particularly erbium lasers, demonstrated success rates up to 64% for all-ceramic restorations with minimal damage to underlying tissues. Ultrasonic instruments effectively disrupted cement layers through vibration and cavitation, offering conservative removal. Specialized mechanical and electrochemical devices showedpotential for improved efficiency and restoration reusability. Traditional mechanical and chemical methods, though effective, carried a higher risk of tooth and restoration damage.Conclusion: Modern removal techniques, particularly laser and ultrasonic systems, provide safer and more conservative alternatives to traditional methods. Their integration into clinical practice can improve patient outcomes, reduce complications, and enhance the longevity of dental structures. Continued research and technological refinement are warranted to standardize protocols and furtherimprove clinical efficiency.